Study of Total Phenolic, Total Flavonoid, Scopoletin Contents and Antioxidant Activity of Extract of Ripened Noni Juice - Lia Meilawati; Teni Ernawati; Rizna Triana Dewi; Megawati Megawati; Sukirno Sukirno (Jurnal Kimia Terapan Indonesia, 2021)
AbstractExtraction of ripened noni juice has been carried out using ethanol and water. The purpose of this study was to determine the total phenolic, total flavonoids, scopoletin, content and antioxidant activity of the ripened noni juice extract. The activity test was carried out on the ripened noni juice extract without and with the addition of ethanol and water solvent. The phytochemical assays of ethanol extract of the ripened noni juice showed that thetotal phenolic content was 3,94 mg gallic acid equivalent/g extract, the total flavonoids was 0,59 mg quercetin equivalent /g extract, the IC50 antioxidant activity was 24,92 mg/L, scopoletin content was 2,45 mg/gram.Keywords : Antioxidant, flavonoids, phenolic, ripened noni juice, scopoletin